EUGENOL AND GLYCYRRHIZIC ACID INHIBIT COLON CARCINOGENESIS VIA INDUCING APOPTOSIS AND REDUCING OXIDATIVE STRESS IN AZOXYMETHANE-TREATED RATS - Dogru, Mustafa Selim; Atessahin, Ahmet; Ceribasi, Ali Osman; Karakurt, Serdar (Parlar Scientific Publications (P S P), 2020)
The high mortality of cancer is one of the crucial problems in human beings especially colorectal carcinoma (CRC) with higher morbidity (2nd grade) required new prevention approaches. The aim of this study was to investigate the potential chemopreventive effects of eugenol (EU) and glycyrrhizic acid (GA) on azoxymethane (AOM)-induced colorectal cancer in rats. In the study, 80 Sprague Dawley male rats were used. The rats were randomly divided into eight groups as follows: Control, AOM (15mg/kg bw., sc, once a week for two weeks), EU (EU 100 mg/kg bw., gavage), GA (GA 15 mg/kg bw., gavage), EU+GA, AOM+EU, AOM+GA, and AOM+EU+GA. All the rats except those in the control and AOM groups were treated with EU and GA for 16 weeks. At the end of the study, the colon tissues were examined in terms of Aberrant Crypt Foci (ACF) and histopathology. Malondialdehyde (MDA) and reduced glutathione (GSH) levels, as well as superoxide dismutase (SOD) and catalase (CAT) activities, were evaluated biochemically in colon tissue. In addition, Bax, Bel 2 and p53 protein expressions in colon samples were determined by Western blotting. In the colon tissues of rats treated with AOM, MDA levels and CAT activities were found out to increase, whereas GSH levels and SOD activities decreased. On the other hand, AOM treatment increased Bcl-2/Bax ratio but downregulated p53 and Bax expressions. In the histopathological examination, an increase was detected in ACF numbers and malignant tumoral lesions. The use of EU+GA decreased oxidative stress and ACF numbers, induced apoptosis, and upregulated p53 expression in AOM-treated rats. In conclusion, EU+GA was determined to be more effective against colorectal cancer when compared with the other treatment groups.
Keywords: ACF; azoxymethane; eugenol; glycyrrhizic acid; oxidative stress